Trame sottili Voci diverse per un vestiario sentimentale - Mancino, Emanuela (FrancoAngeli, 2021)
Things - and even more so clothes and fabrics - possess a further way of being, a sort of cavity in which traces and footprints remain of those who use them, have used them or created them, have desired or chosen them. In addition, in their space, we find our ability to give word to their presence and ours. Clothes possess the particular ability of taking us into the world scene with our body, of getting us out of a condition of disappearance, subtraction or naked intimacy. This text recovers the poetic sense of our bonds with an original feeling that lies in the experience of the body, its symbolic values, the strength and voice of our bonds with the garments and the fabrics of the world. Clothes, from everyday objects, become world again when we learn to glimpse in them the chance of recognizing ourselves, of awakening their history and ours, of retracing and interweaving those subtle threads that allow us to speak the language of belongings. The voices in this plural text are placed within a large and durable research facility that is part of a philosophical approach to the experience aesthetics and the poetic-metaphorical aspect of existence. This book is aimed at those who have already tried or want to try to subtract things from their apparent silence, going through new educational sentences, aimed at the history of ourselves as well as the history of others, going through an everyday life pedagogy that can't wait to have a voice, in order to create horizons of meaning that dress up and dress us up with intimacy when we realize that we know how to give - and live - new space to what is next, so close that it becomes - sometimes - invisible.